Computed tomographic assessment of right ventricular long axis strain for prognosis after transcatheter aortic valve replacement. Issue 149 (April 2022) - Aquino, Gilberto J.; Decker, Josua A.; Schoepf, U. Joseph; Carson, Landin; Fiegel, Matthew; Paladugu, Namrata; Brandt, Verena; Yacoub, Basel; Emrich, Anna Lena; Kroencke, Thomas; Burt, Jeremy R.; Bayer, Richard; et al.
Abstract: Objectives: To investigate the predictive value of right ventricular long axis strain (RV-LAS) derived by cardiac computed tomography angiography (CCTA) for mortality in patients with aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Methods: We retrospectively included patients with severe AS undergoing TAVR (n = 168, median 79 years). Parameters of RV function including RV-LAS and RV ejection fraction (RVEF) were assessed using pre-procedural systolic and diastolic CCTA series. The tricuspid annulus diameter (TAD) and diameter of the main pulmonary artery (mPA) were also assessed. All-cause mortality was recorded post-TAVR. Cox regression was used and results are presented with hazard ratio (HR) and 95% confidence interval (CI). Harrell's c-index was used to assess the performance of different models and the likelihood ratio test was used to compare nested models. Results: Thirty-eight deaths (22.6%) occurred over a median follow-up of 21 months. RV-LAS > -11.42% (HR 2.86, 95% CI 1.44–5.67, p = 0.003), LVEF (HR 0.98, 95% CI 0.96–0.996; p = 0.02), TAD (HR 1.05, 95% CI 1.01–1.10, p = 0.02) and mPA diameter (HR 1.09, 95% CI 1.02–1.16, p = 0.01) were associated with mortality on univariable analysis. In a multivariable model, only RV-LAS (HR 2.36, 95% CI 1.04–5.36, p = 0.04) remained as an independent predictor of all-cause mortality. RV-LAS significantly improved the predictive power of the Society of Thoracic Surgeons Predicted Risk of Mortality (STS-PROM) (c-index 0.700 vs 0.637; p = 0.01). Conclusion: RV-LAS was an independent predictor of all-cause mortality in patients with severe AS undergoing TAVR, outperformed anatomical markers such as TAD and mPA diameter, and could potentially improve the current risk-stratifying tool.